Repeated modification of early limb morphogenesis programmes underlies the convergence of relative limb length in Anolis lizards (2012)
The independent evolution of similar morphologies has long been a subject of considerable interest to biologists. Does phenotypic convergence reflect the primacy of natural selection, or does development set the course of evolution by channelling variation in certain directions? Here, we examine the ontogenetic origins of relative limb length variation among Anolis lizard habitat specialists to address whether convergent phenotypes have arisen through convergent developmental trajectories. Despite the numerous developmental processes that could potentially contribute to variation in adult limb length, our analyses reveal that, in Anolis lizards, such variation is repeatedly the result of changes occurring very early in development, prior to formation of the cartilaginous long bone anlagen.